The rate of liver impairment, character of bacteremia and serum bactericidal activity in patients with cirrhosis - Krutikov S.N.; Krivorutchenko Yu.L.; Postnikova O.N.; Krutikova M.S.; Logadir T.A. (Medičnì Perspektivi)
Dependence of prevalence and severity of bacteremia on the rate of liver impairment, serum bactericidal activity (SBA), and serum concentrations of C-reactive protein (CRP) and granulocyte colony-stimulating factor (G-CSF) in 80 hospitalized patients with liver cirrhosis (LC) have been studied. It was shown that risk factors associated with the development of bacteremia are high by Child-Pugh score and low SBA, CRP and G-CSF levels. Patients with LC, class A had the highest SBA, CRP and G-CSF levels. Still 14,3% of them developed less severe bacteremia associated with one type of microorganisms isolated from blood. Patients with LC, class B had intermediate SBA, CRP and G-CSF levels. They developed severe bacteremia in 52,6% of cases and less severe bacteremia – in 21,1% of cases. Patients with LC, class C had low SBA, CRP and G-CSF levels. They developed severe bacteremia in 62,5% of cases and less severe bacteremia – in 25% of cases.